Does plot size matter? Evidence from maize production in Babati District, Tanzania. Issue 2 (17th February 2016) - Baha, Michael Raphael
ABSTRACT: Debates about optimal farm structure and size have a long history in agricultural economics. Agricultural and development economists argue for an inverse relationship between farm size and productivity, but debates around this remain inconclusive. This article provides a case from maize production in Babati District, Tanzania. The efficiency level of 122 sampled smallholder farmers was estimated and found to be 62.3%, suggesting 37.7% of inefficiencies. A U-shape relationship between plot size and efficiency scores was found. There was high efficiency at plots <2 ha, compared to 2 ha and 3 ha, followed by efficiency at plots >4 ha. Policies stimulating small- and large-scale farms in the country are imperative.